PENGARUH VIRAL MARKETING, CELEBRITY ENDORSEMENT DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE PADA GEN Z WOMEN DI KOTA BATAM - Muhammad Arif Rahman; Husda, Nur Elfi (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
The large number of skincare products and brands that have emerged has created a high level of competition. Every company is required to reach the desired target market. The target market can be achieved through consumer purchasing decisions. This target can be achieved with various factors, some of which are Viral Marketing, Celebrity Endorsement and Brand Image. This research aims to determine the influence of Viral Marketing, Celebrity Endorsement, and Brand Image on Purchasing Decisions for Gen Z Women's Skincare Products in Batam City. This type of research is descriptive quantitative. The research method is multiple linear regression. The sampling technique uses non-probability sampling techniques. The research sample was 97 respondents. Data was processed using the SPSS v25 program. The research results show that Viral Marketing does not have a positive and significant effect on Purchasing Decisions, Celebrity Endorsement has a positive and significant effect on Purchasing Decisions and Brand Image has a positive and significant effect on Purchasing Decisions. The magnitude of the influence of Viral Marketing, Celebrity Endorsement and Brand Image in explaining the Purchasing Decision variable is 70.6%.